Enhanced seasonal contrast of surface mixed layer depth in the North Indian Ocean under a CO2 removal scenario - Shang-Min Long; Chenyi Sun; Zhen Gao; Ming Feng; Xia Qu; Gang Huang; Xingrong Chen (Geoscience Letters)
Abstract The surface mixed layer depth (MLD) of the tropical Indian Ocean is projected to shoal significantly under increased atmospheric CO2, but its further response to subsequent CO2 removal remains unclear. This work investigates this issue utilizing climate models’ simulations under an idealized scenario with symmetric increase and decrease in atmospheric CO2. The results show that the increased CO2-induced basin-wide MLD shoaling recovers rapidly when CO2 decreases. However, the MLD changes display large spatial variations and leave a prominent overall deepening trend in the North Indian Ocean (NIO) but an overall shoaling trend south of 10°S when CO2 returns to its initial level. The former comprises an overall deepened winter deep MLD but shoaled summer MLD, amplifying the seasonal MLD contrast north of 10°N. The overall winter deepening is dominated by a prominent Newtonian cooling over large residual surface warming as the overall winter monsoon changes are weak when CO2 level is restored. While the overall summer shoaling primarily results from the prominent monsoon weakening, the shoaling effect from reduced wind overwhelm the Newtonian cooling by reducing wind stirring, suppressing latent heat loss and increasing cloud-related radiative flux. In contrast, the overall MLD shoaling south of 10°S displays minor seasonal differences due to persistent weakening in the trade winds year-round, resulting from an enhanced Southern Ocean warming. Despite complicated ocean–atmosphere coupling processes in the overall Indian Ocean MLD trend, the residual sea surface warming and distinct winter and summer changes are essential. The results highlight the compound and coupled effects of different surface forcing on MLD changes under external forcing and imply that while CO2 removal actions can largely recover the Indian Ocean MLD shoaling and seasonal cycle changes induced by anthropogenic warming, nonlinear atmospheric response may leave asymmetric changes in oceanic conditions and hence climatic and biological systems.